2012
DOI: 10.1073/pnas.1114168109
|View full text |Cite
|
Sign up to set email alerts
|

The activity of Gli transcription factors is essential for Kras-induced pancreatic tumorigenesis

Abstract: Pancreatic ductal adenocarcinoma (PDAC), one of the most aggressive human malignancies, is thought to be initiated by KRAS activation. Here we find that transcriptional activation mediated by the Gli family of transcription factors, although dispensable for pancreatic development, is required for Kras-induced proliferation and survival in primary pancreatic epithelial cells in culture and for Kras-driven pancreatic intraepithelial neoplasia and PDAC formation in vivo. Further, ectopic Gli1 activation in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
118
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 72 publications
3
118
0
1
Order By: Relevance
“…Recently, we demonstrated that the loss of GLI1 in a genetically engineered mouse model (GEMM) blocks the progression of pancreatic intraepithelial neoplasms (PanIN) induced by oncogenic KRAS (10). In agreement with these findings, using a transgenic model overexpressing a repressor form of the transcription factor GLI3 to antagonize GLI1 activity, Rajurkar et al (11) showed a requirement for this transcription factor in pancreatic cancer initiation. Furthermore, several studies demonstrate that blocking Sonic Hedgehog (SHH), the most well established upstream regulator of GLI1, down-regulates GLI1 expression and inhibits tumor growth in established xenograft models, suggesting a role for GLI1 in pancreatic tumor progression (13).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Recently, we demonstrated that the loss of GLI1 in a genetically engineered mouse model (GEMM) blocks the progression of pancreatic intraepithelial neoplasms (PanIN) induced by oncogenic KRAS (10). In agreement with these findings, using a transgenic model overexpressing a repressor form of the transcription factor GLI3 to antagonize GLI1 activity, Rajurkar et al (11) showed a requirement for this transcription factor in pancreatic cancer initiation. Furthermore, several studies demonstrate that blocking Sonic Hedgehog (SHH), the most well established upstream regulator of GLI1, down-regulates GLI1 expression and inhibits tumor growth in established xenograft models, suggesting a role for GLI1 in pancreatic tumor progression (13).…”
supporting
confidence: 68%
“…The success of these trials has been mixed, possibly due to the complexity of the signaling processes involved in pancreatic cancer progression. Recently, our group and others have identified GLI1 as a mediator in the process of cellular transformation in vivo where loss of GLI1 in the presence of oncogenic KRAS inhibited late stage PanIN formation and pancreas cancer initiation (10,11). However, the significance of GLI1 expression and the molecular mechanisms regulating expression in pancreatic cancer progression are conflicting.…”
Section: Discussionmentioning
confidence: 94%
“…These pathways modulate GLI1 activity mainly via regulation of the expression of this transcription factor (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we provide evidence of a novel regulatory mechanism involving the interaction of components of the TGF␤ pathway (SMAD proteins) modulating GLI1 activity in cancer cells.…”
Section: Discussionmentioning
confidence: 75%
“…These findings support the notion that increased expression of GLI1 is sufficient for the development of a subset of tumors. GLI1 activity is regulated by different oncogenic cascades, including the HEDGEHOG, EGFR, RAS, and TGF␤ pathways (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It has been demonstrated that malignant transformation induced by some of these cascades requires an intact GLI1 transcriptional activity (17,20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation